Pre-university Measures and University Performance: A Multilevel Structural Equation Modeling Approach - Vista, Alvin; Alkhadim, Ghadah S. (Frontiers in Education, 2022)
This study investigated the relationship between three pre-university measures (high school grade point average, the General Aptitude Test, and the scholastic achievement admission test) and university performance. Further, this study examined the mediating role of preparatory year in the relationship between the three pre-university measures and university performance. Data from 330,684 undergraduate students from 23 universities across the Kingdom of Saudi Arabia were analyzed using a multilevel structural equation modeling approach. Pre-university measures were consistent in predicting pre-university performance, and the scholastic achievement admission test was the strongest predictor among the pre university measures.. The findings supported previous results—that preparatory year has a positive effect on university performance, and that both pre-university measures and preparatory year performance predict eventual performance at the university, including whether the student stays regular and eventually completes university studies. These results have implications for the importance of a preparatory year and this study adds to the body of work that can inform further cost-benefit studies of such preparatory programs.